Visual analysis of seismic simulation data - Gerhardt, F.J.; Meyer, J. (IEEE Symposium on Visual Analytics Science and Technology, 2008 : proceedings, Columbus, Ohio, USA, October 21-October 23, 2008, 2008)
Seismic simulations use finite element methods to describe ground motion. The results of such numerical simulations are often difficult to interpret for decision makers. We describe a terrain rendering engine that uses photorealistic metaphors to represent typical terrain properties without representing an actual terrain. In the context of ground motion, a simulation of the effects of various types of earthquakes on buildings has been conducted. Usually, such structural response simulations are carried out independently and are being visualized separate from the ground motion simulation. We combine the results from both simulations in an interactive, hybrid visualization so that decision makers (first responders and emergency management agencies) are provided with a photo-realistic, simulated view of various earthquake scenarios, enabling them to study the effect of various earthquakes on buildings typical for a rural or urban area. We present a method for visually analyzing large-scale simulation data from different sources (ground motion simulation and structural response simulation) using photorealistic metaphors. We have implemented an intuitive, interactive system for visual analysis and inspection of possible effects of various types of earthquakes on an inventory of buildings typical for a particular area. The underlying rendering system can be easily adapted for other simulations, such as smoke plumes or biohazards.